Subalterns and Sovereigns: An Anthropological History of Bastar (1854-2006) - Sundar, Nandini (New Delhi ; Oxford University Press, 2007)
Articles with reference to Bastar District, India.
Includes bibliographical references (p. [301]-319) and index.
Keywords: Bastar (India : District) -- History, Ethnic relations -- 19th century. -- Political aspects